Chars and Activated Carbons Prepared from Asturian Apple Pulp - Fernandez, Elena; Centeno, Teresa A.; Stoeckli, Fritz (My University, 2001)
Asturian apple pulp was carbonised under nitrogen at 400ºC and 750ºC and subsequently activated with CO2 at 750ºC. The resulting active carbon exhibited properties in line with those expected from precursors of vegetable origin, with the carbonisation stage appearing to have only a limited influence on the final porosity. In the case of carbonisation at 400ºC, the initial micropore system of the char was accessible to dichloromethane, CO2 and water, but presented a strong gate effect at ca. 0.35-0.40 nm. The pore volume, W0, was equal to 0.13 cm3/g and the average pore width 0.70 nm. The pore size distribution was obtained from CO2 adsorption at 0ºC, using isotherms derived from computer modelling. With the char prepared at 750ºC, the initial porosity was only accessible to water and its presence was confirmed by extrapolation of W0 for the activated carbons.